(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: Describe the current status of cervical cancer vaccination among female high school students at Chu Van An Primary, Secondary and High School in 2025 and some related factors. Research method: A cross-sectional descriptive study design was conducted on 108 female students from grades 10-12 at Chu Van An Primary, Secondary and High School in 2025, collected through a prepared questionnaire. Results: The rate of cervical cancer vaccination was 36.1%; of which the rate of full vaccination was 25.9%. The most common reason for vaccination was to prevent the disease (76.9%). The reason for not being vaccinated was fear of post-vaccination reactions (34.8%) and family economic conditions (30.4%). 23.2% did not know about the vaccine. In the future, 87% of the subjects were willing to get vaccinated. There is a correlation between the factor of having parents who are health workers and the status of cervical cancer vaccination (p<0.05). Conclusion: The rate of cervical cancer vaccination in the study subjects is not high (36.1%). Due to the subjects’ concerns about post-vaccination reactions, family economic conditions and not knowing about the vaccine. There is a correlation between the factor of having parents who are health workers and the status of cervical cancer vaccination.